Co-creation of Activity Spaces in an amateur dance group: interactional construction of the Teaching Space - Smart, Naomi; Szczepek Reed, Beatrice (Frontiers in Communication, 2025)
This paper explores the co-construction of ‘Activity Spaces’ within weekly rehearsals of an amateur, mixed-level dance company. Data are taken from field notes, participant observation experience, and video recordings. An earlier analysis identified three canonical spatial divisions that participants co-create during ballet rehearsals: the ‘Dancing Space’, the ‘Teaching Space’, and the ‘Peripheries’. The present study shows that these Activity Spaces are not demarcated physically but are instead entirely co-constructed through participants’ own multi-modal actions within the rehearsals. An important aspect of this co-construction are the participation roles dancer, choreographer, participants not currently dancing. Participants’ contributions to activities are in part negotiated through their turn design and their positioning within and across Activity Spaces. The analysis focuses in on the ‘Teaching Space’, how it is assigned meaning within the group, and how it is reconfigured according to participants’ needs through their mobilisation of multi-modal resources. Of special interest are moments in which a member takes up or relinquishes a teaching/choreographing role. Features given attention include bodily orientations, such as dancers’ positioning of themselves to have visual access to the choreographer; prosodic features, such as choreographers’ use of raised volume relative to surrounding interaction; and verbal contributions from the choreographer and from dancing and currently-not-dancing participants. Data are in English.